Prevalence of cryptosporidium in children under 5 years of age, immunocompromised patients and high risk persons in Isfahan province - Mehdi Azami; Davod Dorostkar Moghadam (Iranian South Medical Journal, 2008)
Background: Cryptosporidium is an important enteric parasite which causes diarrheal illness in humans and animals worldwide. With attention to the role of cryptosporidium in producing diarrhea and mortality in immunocopromised patients and children under 5 years of age, the present study was designed to identify the prevalence of cryptosporidium and potential risk factors in Isfahan province. Methods: This descriptive study was done in Isfahan province from October 2003 to April 2004. A total of 642 children under 5 years of age, immunocompromised patients and high risk persons selected randomly and their stool samples were studied microscopically using Sheater's Sucrose Flotation technique and stained by modified Ziehl-Neelsen staining method. Results: The overall prevalence of cryptosporidium was 4.7% (30 samples). The prevalence rates of infection were 4.6%, 3.5% and 5.4% in children under 5 years of age, immunocompromised patients and high risk persons, respectively. The highest prevalence of infection (6.2%) belonged to 1-2 years old children in the group of under 5 years of age, 3-4 years in immunocompromised patients group and 5-10 years in high risk persons group (10%, 6.2% and 14.8% respectively). Conclusion: Cryptosporidium is significantly prevalent in children under 5 years of age, immune compromised patients and high risk persons in Isfahan province. Therefore, health policy makers have to design a plan to identify and treat infected subjected with cryptosporidium thus as a result the transmission of the disease can be prevented in the society.